A kinematically unbiased, all-sky search for nearby, young, low-mass stars. Issue 1 (5th November 2019) - Binks, Alexander S; Chalifour, Matthieu; Kastner, Joel H; Rodriguez, David; Murphy, Simon J; Principe, David A; Punzi, Kristina; Sacco, Germano G; Hernández, Jesús
ABSTRACT: The past two decades have seen dramatic progress in our knowledge of the population of young stars of age \!200 Myr that lie within 150 pc of the Sun. These nearby, young stars, most of which are found in loose, comoving groups, provide the opportunity to explore (among many other things) the dissolution of stellar clusters and their diffusion into the field star population. Here, we exploit the combination of astrometric and photometric data from Gaia and photometric data from GALEX (UV) and 2MASS (near-IR) in an attempt to identify additional nearby, young, late-type stars. Specifically, we present a sample of 146 GALEX UV-selected late-type (predominantly K-type) field stars with Gaia -based distances \!125 pc (based on Gaia Data Release 1) that have isochronal ages \!80 Myr even if equal-components binaries. We investigate the spectroscopic and kinematic properties of this sample. Despite their young isochronal ages, only ∼10 per cent of stars among this sample can be confidently associated with established nearby, young moving groups (MGs). These candidate MG members include five stars newly identified in this study. The vast majority of our sample of 146 nearby young star candidates have anomalous kinematics relative to the known MGs. These stars may hence represent a previously unrecognized population of young stars that has recently mixed into the older field star population. We discuss the implications and caveats of such a hypothesis – including the intriguing fact that, in addition to their non-young-star-like kinematics, the majority of the UV-selected, isochronally young field stars within 50 pc appear surprisingly X-ray faint.